Corporate Social Responsibility Disclosure and Earnings Management: Evidence from China - Zhang, Fan (2019)
This paper aims to estimate the relationship between the disclosure of corporate social responsibility (CSR) and earnings management in Chinese listed companies, over a period from 2014 to 2018. Based on prior accounting research, this study applies the cross-sectional modified Jones model to estimates the earnings management indicator: absolute discretionary accruals. The research results show that CSR disclosure negatively correlates to earnings management, which implies that the earnings management behaviour can be constrained through the disclosure of CSR information. This support the transparent reporting hypothesis that is, the more CSR information is disclosed, the more transparent corporate financial reporting will be, and the fewer earnings management behaviour occurs. In addition, this paper finds that the quality of CSR information disclosure is more important than its quantity to reduce earnings manipulation. In this case, Chinese regulators should pay more attention to the quality of CSR reports, rather than requiring more CSR reports.